Strategies for introducing and implementing vaccines for adults into national immunization programs in Europe: Good practices and key insights of the adult immunization board meeting - Sara Boccalini; Angela Bechini; Marco Del Riccio; Birgit Weinberger; Jacek Wysocki; Domenico Martinelli; Ole Wichmann; Tiina Likki; Greet Hendrickx; Pierre Van Damme; Chloé Wyndham-Thomas; Paolo Bonanni; et al. (Human Vaccines & Immunotherapeutics)
In April 2024, the Adult Immunization Board convened a technical meeting to explore the latest strategies and identify exemplary approaches regarding the implementation of vaccines for adults into Europe’s National Immunization Programs (NIPs). The meeting was built around three pillars: decision making for introducing a new vaccine, implementation, monitoring, and evaluation. The increasing number of new vaccines available in a context of competing health priorities warrants transparent and evidence-based decision-making processes for vaccine introduction. In Europe, burden of disease, vaccine efficacy or effectiveness, and safety are universally used decision-making criteria. While economic evaluations and the quality of evidence are being increasingly considered, public acceptance, equity, and operational criteria remain underutilized. Vaccine implementation requires planning and coordination. Implementation activities discussed during the meeting were vaccine program goals, target population identification, communication, training of healthcare professionals, and involvement of pharmacists. Once operational, NIPs are to be monitored in terms of safety, effectiveness, and impact. Implementation science as well as behavioral and cultural insights can be used to identify tangible interventions to improve uptake. Meeting discussions allowed to identify adult vaccine implementation barriers and possible strategies to overcome them. Enhanced cooperation and coordination throughout the Europe region were recognized as critical components of progress.